Application Of Fuzzy Ensembles For Optimal Distribution Of Power In Electrical Networks - Guediri, A.; Ben Attous, D. (University of Eloued جامعة الوادي, 2011)
Optimal power flow calculation (OPF), used to optimize specific aspects of power system operations, usually employ standard mathematical programming techniques. These techniques are not suitable to handle many practical considerations encountered in power systems, including the uncertainty of the operational constraints [1]. They can be relaxed temporarily, if necessary, to obtain feasible solutions. For taking well into account this type of constraints, one proposes in this work the application of a method based on fuzzy sets to the OPF problem. The developed method has been tested on standard scale power systems (IEEE30bus).
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 01
Keywords: optimal power flow, Fuzzy optimization, Fuzzy mathematical programming.